The Importance of Stem Photosynthesis for Two Desert Shrubs Across Different Groundwater Depths - Liu, Ran; Feng, Xiaolong; Li, Congjuan; Ma, Jie; Wang, Yugang; Li, Yan (Frontiers in Plant Science, 2022)
Water availability could alter multiple ecophysiological processes such as water use strategy, photosynthesis, and respiration, thereby modifying plant water use and carbon gain. However, a lack of field observations hinders our understanding of how water availability affects stem photosynthesis at both organ and plant levels of desert shrubs. In this study, we measured gas exchange and oxygen stable isotopes to quantify water sources, stem recycling photosynthesis, and whole-plant carbon balance in two coexisting Haloxylon species (Haloxylon ammodendron and Haloxylon persicum) at different groundwater depths in the Gurbantonggut Desert. The overall aim of the study was to analyze and quantify the important role of stem recycling photosynthesis for desert shrubs (Haloxylon species) under different groundwater depths. The results showed that (1) regardless of changes in groundwater depth, H. ammodendron consistently used groundwater and H. persicum used deep soil water as their main water source, with greater than 75% of xylem water being derived from groundwater and deep soil water for the two species, respectively; (2) stem recycling photosynthesis refixed 72–81% of the stem dark respiration, and its contribution to whole-plant carbon assimilation was 10–21% for the two species; and (3) deepened groundwater increased stem water use efficiency and its contribution to whole-plant carbon assimilation in H. persicum but not in H. ammodendron. Our study provided observational evidence that deepened groundwater depth induced H. persicum to increase stem recycling photosynthetic capacity and a greater contribution to whole-plant carbon assimilation, but this did not occur on H. ammodendron. Our study indicates that stem recycling photosynthesis may play an important role in the survival of desert shrubs in drought conditions.